Factors of influence on the formation and development of human potential - N. A. Baltacheeva; A. A. Torba (Вестник Северо-Кавказского федерального университета, 2022)
The relevance of the research topic is due to the need to revise the indicators that influence the formation and development of human potential, their additions and extensions based on large-scale digitalization and high technology of modern society. Based on the analysis of the available scientific literature, the article considers the factors of influence on the formation and development of human potential as the basis of the modern economy. The analysis of the essence of the concept of «innovative person» is carried out, the problems of the conceptual and categorical apparatus of interpretation of this definition and its content are revealed. Four groups of factors have been formed depending on the age period, and «predestining» factors – «macrofactors» – have been identified, their characteristics and content are presented. A mathematical analysis of the interdependence of the components of the human development index is carried out, on the basis of which the necessity of introducing the concept of «scientific potential index» is justified, the author’s method of its calculation is developed and proposed.